Launching a business : the first 100 days - Barringer, Bruce R. (New York : Business Expert Press, 2013)
This is a hands-on book that focuses on the tasks that a new business owner must complete in the first 100 days of launching a business. Think of it this way. Imagine you've conceived a business idea, written a business plan, raised seed capital, and are set to launch your business on October 1. Now, what would you actually do on October 1, October 2, October 3, and so forth? How would you set your priorities? How would you know which tasks are the most urgent? Although the answers to these questions vary depending on the business, there are a set of key activities that all businesses must accomplish to get their businesses off to a good (and legally proper) start. Examples include securing the proper business licenses and permits, setting up a bookkeeping system, negotiating a lease, buying insurance, entering into contracts with vendors, recruiting and hiring employees, making the first sale, and so on. Broader issues such as developing a business model and building a brand will be touched upon. But the primary focus of the book will be on the practical issues that a business owner needs to accomplish, and needs to accomplish correctly, to get a business off to a good start.
Includes index.
Keywords: New business enterprises -- Management